Burdock (Arctium lappa L.) root attenuates preneoplastic lesion development in a diet and thioacetamide-induced model of steatohepatitis-associated hepatocarcinogenesis - Romualdo, Guilherme R. [UNESP]; Silva, Elizangela dos Anjos; Da Silva, Tereza C.; Aloia, Thiago P. A.; Nogueira, Marina S.; De Castro, Inar A.; Vinken, Mathieu; Barbisan, Luís F. [UNESP]; Cogliati, Bruno (Wiley, 2020)
Nonalcoholic steatohepatitis (NASH) is considered growing risk factor for hepatocellular carcinoma development in high-income countries. Diet- and chemically induced rodent models have been applied for the translational study of NASH-associated hepatocarcinogenesis due to their morphological and molecular similarities to the corresponding human disease. Arctium lappa L. (burdock) root tea has been extensively consumed in Traditional Chinese Medicine due to its potential therapeutic properties. Indeed, the bioactive compounds of A. lappa root, as the polyphenols, have already showed antioxidant and anti-inflammatory properties in different in vivo and in vitro bioassays. In this study, we investigated whether burdock root ethanolic extract (BRE) administration attenuates NASH-associated hepatocarcinogenesis. Eight-week-old male Wistar rats received choline-deficient high-fat diet for 8 weeks and multiple thioacetamide doses for 4 weeks in order to induce NASH and preneoplastic glutathione-S-transferase pi (GST-P)+ preneoplastic foci. Subsequently, rats were treated with BRE (100 or 200 mg/kg body weight) or vehicle by oral gavage for 2 weeks. BRE displayed high levels of chlorogenic and caffeic acids and BRE administration reduced total fatty acid and lipid hydroperoxide levels, while increasing the activities of antioxidant superoxide dismutase and catalase enzymes in the liver. Furthermore, burdock intervention diminished the size of GST-P+ remodeling preneoplastic lesions (PNLs) and displayed a trend on reducing hepatocyte proliferation (Ki-67) inside them. These findings suggest that short-term exposure to BRE alleviated remodeling PNL development in NASH-associated hepatocarcinogenesis.
Keywords: burdock (Arctium lappa L.); chlorogenic acid; GST-P+ preneoplastic lesions; nonalcoholic steatohepatitis; rat hepatocarcinogenesis